Harmonization of LC-MS/MS Measurements of Plasma Free Normetanephrine, Metanephrine, and 3-Methoxytyramine. (16th May 2021) - Peitzsch, Mirko; Novos, Talia; Kaden, Denise; Kurlbaum, Max; van Herwaarden, Antonius E; Müller, Daniel; Adaway, Jo; Grouzmann, Eric; McWhinney, Brett; Hoad, Kirsten; Woollard, Gerald; Kema, Ido; et al.
Abstract: Background: Plasma-free normetanephrine and metanephrine (metanephrines) are the recommended biomarkers for testing of pheochromocytoma and paraganglioma (PPGL). This study evaluated the status of harmonization of liquid chromatography-tandem mass spectrometry-based measurements of plasma metanephrines and methoxytyramine and clinical interpretation of test results. Methods: 125 plasma samples from patients tested for PPGLs were analyzed in 12 laboratories. Analytical performance was also assessed from results of a proficiency-testing program. Agreement of test results from different laboratories was assessed by Passing-Bablok regression and Bland-Altman analysis. Agreement in clinical test interpretation based on laboratory specific reference intervals was also examined. Results: Comparisons of analytical test results by regression analysis revealed strong correlations for normetanephrine and metanephrine (R ≥ 0.95) with mean slopes of 1.013 (range 0.975–1.078), and 1.019 (range 0.963–1.081), and intercepts of −0.584 (−53.736 to 54.790) and −3.194 (−17.152 to 5.933), respectively. The mean bias between methods was 1.2% (−11.6% to 16.0%) for metanephrine and 0.1% (−18.0% to 9.5%) for normetanephrine. Measurements of 3-methoxytyramine revealed suboptimal agreement between laboratories with biases ranging from −32.2% to 64.0%. Interrater agreement in test interpretation was >94% for metanephrine and >84% for normetanephrine; improvements in interrater agreement were observed with use of harmonized reference intervals, including age-specific cut-offs for normetanephrine. Conclusions: Analytical methods for metanephrines are well harmonized between laboratories. However, the 16% disagreement in test interpretation for normetanephrine suggests use of suboptimal method-dependent reference intervals for clinical decision-making for this metabolite. Improved analytical methods and reference interval harmonization are particularly required for 3-methoxytyramine.